Development of Total Suspended Solids (TSS) Algorithm Based on Visible Spectrum Reflectance of Sentinel-2 Imagery (Case: in Suwung Estuary, Bali) - I Made Yuliara; Ni Nyoman Ratini; Winardi Tjahyo Baskoro; Hendrata Wibisana (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and build a new algorithm model that is suitable for predicting the concentration and spatial distribution of total suspended solids (TSS) in the Suwung estuary in Bali based on the visible spectrum reflectance of Sentinel-2 imagery. A total of 20 water samples were taken at selected coordinates and the time coincided with the Sentinel-2 satellite recording the research location. The TSS concentration of the samples was measured in the laboratory (in-situ) and the bottom of atmosphere reflectance correction (  used the dark object substaction (DOS) method. The development used regression and correlation of in-situ data with imagery. Three algorithm models, namely Budhiman (2014), Guzman & Santaella (2009), and Parwati (2014) were used as an approach to developing a new TSS algorithm (AlgoNew), resulting in the Parwati model as the best model (MAPE = 3.889%, RMSE = 0.386 and R2 = 0.816). The result of AlgoNew model development is , where the MAPE is 3.315%, RMSE = 0.332 and R2 = 0.845. The analysis results show that AlgoNew has smaller errors, is more valid, has stronger correlations, and its implications are more representative and feasible to apply compared to Parwati's algorithm (2014).